STUDY OF BELAT BY-CATCH AND DISCARD IN KUALA MERBAU VILLAGE PULAU MERBAU DISTRICT MERANTI ISLAND REGENCY - Gian Nofrianda Ilyas; Arthur Brown; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTBelat is a passive fishing gear that belongs to a group of traps operatedin the area around the coast.On the operation,belatnot only produce of the main catch but also get the by-catch. This study aims to identify the main results, by-cath and discart. The research method used is survey method by doing direct observation of thebelat catch result and then the catch is identified to fish species, individual numberandfishweight. The results of the descriptive analysis show that the main catches are two types of shrimp that is white shrimp (Penaeus merguiensis) and kekas shrimp (Parapenaepsis sculpilis) with a weight of 18.9 kg. By-catch and discard caught are small fish and young fish,by-catch consistsof 9 species with total weight of 14,49 kg kg and discard consists of 5 types withtotal weight of 4,08 kg.Keywords: Belat, main cath, by cath and discard